HUBUNGAN ANTARA HARGA DIRI DENGAN KECERDASAN INTERPERSONAL GURU TAMAN KANAK-KANAK DI KECAMATAN TAMPAN KOTA PEKANBARU - Tita Sapriyanti; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this research is to know whether there is levels and correlation between self esteem and interpersonal intelligence of kindergarten’s teachers at Tampan District of Pekanbaru City. The samples of this research is kindergarten’ s teachers at Tampan District of Pekanbaru City that consists of 55 teachers. Method of this research is Pearson Product Moment correlation to know the correlation between Self Esteem and Interpersonal Intelligence. The technique of collecting data used questioner in Likert scale form. The technique of analyzing data used scale test and statistic analytical. Based of this research there is level of self esteem in the medium category with the percentage 80,12% and the level of interpersonal intelligence in the medium category with the percentage 78,42%. Based of hypothesis there is any significant positive correlation between self esteem and interpersonal intelligence of kindergarten’s teachers at Tampan District of Pekanbaru City. It could be seen from the result of correlation coefficient that rxy = 0,648 and significant level is 0,000 < 0,05. The level of correlation between self esteem and interpersonal intelligence of kindergarten’s teachers is in the highcategory with the rank of determinant coefficient in the amount of KD = r² x 100% = 41,99%, it means that self esteem affect interpersonal intelligence as much as 41,99%.Key Words: Self Esteem, Interpersonal Intelligence